2023
DOI: 10.3390/biology12050679
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Markers Associated with Milk Production and Thermotolerance in Holstein Dairy Cows Managed in a Heat-Stressed Environment

Abstract: Dairy production in Holstein cows in a semiarid environment is challenging due to heat stress. Under such conditions, genetic selection for heat tolerance appears to be a useful strategy. The objective was to validate molecular markers associated with milk production and thermotolerance traits in Holstein cows managed in a hot and humid environment. Lactating cows (n = 300) exposed to a heat stress environment were genotyped using a medium-density array including 53,218 SNPs. A genome-wide association study (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Cheruiyot et al [ 41 ] found eight enriched genes in the glutamatergic synapse pathway associated with heat tolerance in Australian Holstein cattle. In a similar study, Zamorano-Algandar et al [ 42 ] indicated that the glutamatergic synapse pathway was associated with MY in US Holstein affected by heat stress.…”
Section: Resultsmentioning
confidence: 91%
“…Cheruiyot et al [ 41 ] found eight enriched genes in the glutamatergic synapse pathway associated with heat tolerance in Australian Holstein cattle. In a similar study, Zamorano-Algandar et al [ 42 ] indicated that the glutamatergic synapse pathway was associated with MY in US Holstein affected by heat stress.…”
Section: Resultsmentioning
confidence: 91%
“…The candidate gene approach is a strategy used to screen genetic markers associated with a particular trait of interest by focusing on specific genes that are known or hypothesized to be involved in the expression of that trait [73,74]. This approach has been applied to many animal species [75,76], including donkeys [77], for identifying genetic markers associated with production traits such as the growth rate, milk yields, and reproductive performance. By focusing on specific genes that are known or hypothesized to be involved in the expression of the trait of interest, this approach can increase the efficiency of genetic marker discovery and accelerate the development of genomic selection tools for donkey breeding programs.…”
Section: Candidate Gene Approach For the Screening Of Genetic Markers...mentioning
confidence: 99%
“…that tend to be polygenic, and as a result, many genetic variants, each with small effects contribute to the phenotype. In these cases, the heat tolerance trait has been associated with a number of QTL regions and candidate genes ( 14 , 15 , 18 , 92 ). This polygenicity of a trait can be a challenge in achieving rapid genetic progress for heat tolerance in dairy cattle, particularly in cases when the heritability of a trait is low.…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...mentioning
confidence: 99%
“…Identifying genome-wide markers and pathways underpinning the genetic mechanisms that increase thermotolerance in dairy cattle is at the infancy stage, but it is gaining momentum considering the increasing challenges imposed by climate change, as shown by the recent increase in published studies ( 2 , 11 , 12 , 14 , 18 , 92–96 ). Genome-wide association studies are most commonly used to test tens if not hundreds of thousands of genomic variants to find those statistically associated with heat tolerance traits in cattle.…”
Section: Genomic Regions and Candidate Genes Associated With Heat Tol...mentioning
confidence: 99%
See 1 more Smart Citation